Website Quality, Brand Awareness and Purchase Intention: Online Property Purchase Behaviour - Budiarti, Rima; Parma Dwi Widy Oktama (Bina Nusantara University, 2025)
This paper aims to look at online property purchase behavior during the COVID-19 pandemic by consumers as seen from purchase intention on the influence of website quality, brand awareness, and smart lifestyle. Data were collected using a questionnaire through online survey. Data were analyzed using SmartPLS. The results show that the quality of websites (QW) has a significant and positive influence on smart lifestyle (SL) and purchase intention (PI). Brand awareness (BA) also has significant and positive influences on SL and PI. A positive influence and a significant influences were also found between SL and PI. This study has strengthened property purchase behavior theory is influenced by the quality of websites, brand awareness, and smart lifestyle during the COVID-19 pandemic. Based on this research, in line with the smart lifestyle in the community, the property marketplace company must improve the quality of the website by making it more accessible to anyone and increasing brand awareness, especially in the Generation X and Generation Y groups who are very connected online and are potential buyers or property tenants.